2014
DOI: 10.1021/jo501526a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction for the Synthesis of Benzimidazol-2-ones, Imidazo[5,4-b]-, and Imidazo[4,5-c]pyridin-2-ones via the Rearrangement of Quinoxalin-2-ones and Their Aza Analogues When Exposed to Enamines

Abstract: A synthetically useful protocol has been developed for the preparation of highly functionalized N-pyrrolylbenzimidazol-2-ones. The reaction of variously substituted 3-aroyl- and 3-alkanoylquinoxalin-2(1H)-ones with commercially available enamines in acetic acid results in a rapid rearrangement and formation of N-pyrrolylbenzimidazol-2-ones in modest to excellent yields. The key step of the rearrangement involves the novel ring contraction of 3-aroyl- and 3-alkanoylquinoxalin-2(1H)-ones with enamines. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In contrast to the rearrangements of 3-aroyl-quinoxalin-2­(1 H )-ones that occur with commercially available enamines and enamines generated in situ from ammonium acetate and the corresponding methylaryl­(hetaryl)­ketones, rearrangements of 3-aroyl-quinoxalin-2­(1 H )-ones considered in this work, proceeding under the action of enamines generated in situ from malononitrile and secondary amines or primary alcohols, allow us to introduce pharmaceutically significant piperazine, piperidine, morpholine, pyrrolidine ring systems, and diethylamine and alkoxyl groups into the rearrangement products in a one-pot process, which is an undeniable advantage of the described method over other methods of synthesis of polysubstituted pyrroles.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to the rearrangements of 3-aroyl-quinoxalin-2­(1 H )-ones that occur with commercially available enamines and enamines generated in situ from ammonium acetate and the corresponding methylaryl­(hetaryl)­ketones, rearrangements of 3-aroyl-quinoxalin-2­(1 H )-ones considered in this work, proceeding under the action of enamines generated in situ from malononitrile and secondary amines or primary alcohols, allow us to introduce pharmaceutically significant piperazine, piperidine, morpholine, pyrrolidine ring systems, and diethylamine and alkoxyl groups into the rearrangement products in a one-pot process, which is an undeniable advantage of the described method over other methods of synthesis of polysubstituted pyrroles.…”
Section: Resultsmentioning
confidence: 98%
“…In our previous work, the reactions of 3-aroylquinoxalin-2­(1 H )-ones and their 5- and 7-aza-analogues, namely, 3-benzoylpyrido-[3,2- b ]­pyrazin-2­(1 H )-one and 3-benzoylpyrido­[3,4- b ]-pyrazin-2­(1 H )-one, with enamines in acetic acid, were found to give variously substituted 1-[pyrrol-4­(and 5)-yl]-benzimidazol-2­(3 H )-ones through the quinoxalinone–benzimidazolone rearrangement. In these examples, commercially available enamines were used, namely, methyl- and ethyl-3-aminocrotonates (a) and enamines generated in situ in the reactions of variously substituted acetophenone derivatives with ammonium acetate (b) . Assuming that the enamine triatomic moiety is an integral part of amidines and imino esters and can be easily generated by the interaction of amines with nitriles with an active methylene group, in this paper, we present the results of studies of reactions proceeding in a multicomponent system containing aroylquinoxalinones, malononitrile, and various nucleophilic reagents (amines and alcohols) in the presence of acetic acid (c) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, we discovered the acid‐catalyzed rearrangement of 3‐aroylquinoxalin‐2‐ones into 2‐(benzimidazol‐2‐yl)quinoxalines when exposed to 1,2‐benzenediamines [8] . In the last two decades, we have published a series of works on the rearrangement of quinoxalin‐2‐ones via the proposed spiro‐quinoxalinone [9] intermediates ( A ) into 2‐hetarylbenzimidazoles [9a–h] ( B , Type I) as well as 1‐hetarylbenzimidazolones in cases of enamine nucleophiles ( C , Type II, Scheme 1), [9i–k] thus opening a simple way to access various 2‐hetarylbenzimidazoles and 1‐hetarylbenzimidazolones according to the S N (ANRORC) mechanism (i. e., via sequential steps of addition of nucleophile, ring‐opening and ring‐closing) [10] . It was shown that the type of rearrangement may depend on the fact if tautomerizable hydrogen is available or not in the spiro‐forming ring within A .…”
Section: Methodsmentioning
confidence: 99%
“…In this theoretical work, extensive DFT calculations at the PW6B95‐D3+COSMO‐RS//TPSS‐D3+COSMO level in acetic acid solution (see below for computational details) are performed to explore the detailed free‐energy paths for two typical rearrangements of 3‐benzoylquinoxalin‐2‐one ( 1 Q ) with 1,2‐benzendiamine ( 1 a ) [8] and methyl 3‐amonocrotonate ( 1 b ), [9i] which selectively leads to 2‐(benzimidazol‐2‐yl)quinoxaline (Type I) and two N ‐pyrrolyl‐substituted benzimidazol‐2‐ones (Type II), respectively. It is shown that while the former reaction is initiated by a site‐selective N⋅⋅⋅C condensation at the protonated benzoyl group of 1 Q , the latter can be initiated by two C⋅⋅⋅C nucleophilic additions at both protonated benzoyl and imine sites of 1 Q that eventually leads to two isomeric products.…”
Section: Methodsmentioning
confidence: 99%